INGGRIS INGGRIS - Riza Azizy; Dedi Rianto Rahadi (Jurnal Akuntansi, Manajemen dan Ekonomi, 2021)
Training is a company strategy to improve employee performance competencies. However, in the current Covid 19 pandemic, companies cannot conduct training directly because of the government's rules to cdo work and study activities from home. During the Covid 19 pandemic, companies tried to develop employee performance skills, virtual training is one of the methods used to improve employee performance during the COVID-19 pandemic. Bank Mandiri use virtual training solutions to provide training for employees to maintain employee performance so that the company's goals could be achieved even in difficult circumstances such as the current Covid 19 pandemic. The study aims to determine whether virtual training has an effect on improving the performance of Bank Mandiri employees by using qualitative research to describe facts about an incident at Bank Mandiri and a situation that occurred during the COVID-19 pandemic. Data was collected using a survey method by distributing questionnaires to employee respondents. The results showed that the Virtual Training conducted by Bank Mandiri had a very good effect on improving the performance of Bank Mandiri employees.